Rapid And Efficient Purification Method Of Phospholipase A2 From Acanthaster Planci - IMELDA KRISANTA ENDA SAVITRI; FERA IBRAHIM; MUHAMAD SAHLAN; ANONDHO WIJANARKO (International Journal of Pharma and Bio Sciences, 2011)
Rapid and efficient purification method of the phopholipase A2 (PLA2) from the crown-of-thorns starfish Acanthaster planci was done. It was developed without using separation column and taken less time around one day purified. Compare to common procedure that was done by purification measurement using several columns chromatography and was known taken several days, this purification method is more simplify. This purification method use only 30 minutes heat treatment on 60oC and then is fractionated by 20% saturated ammonium sulfate precipitation. The protein complex was analyzed by one dimensional sodium dodecylsulfate polyacrylamide gel electrophoresis. PLA2 is obtained an excellent overall yield with a final enzyme activity was similar to result of common procedure using four columns chromatography.